Pemanfaatan Buah Sisa Sebagai Bioetanol dan Pupuk Organik - Ricky Yadi; Eddifa Rahman; Vetrio Monandes (Dinamika Lingkungan Indonesia, 2021)
The needs for added value of agricultural products is increasing, both in the form of health benefits and of reducing pollution waste. The sorting-out fruits that are just wasted can still be used as materials that have added value. In general, fruits contain glucose which is the basic ingredient in processing of bioethanol. Even though the quality has decreased, it still contains glucose which can then be fermented into bioethanol or organic fertilizer. Recently, the pharmaceutical and food and beverage industries require a large supply of bioethanol for further processing according to the industrial needs. Meanwhile, agricultural land is increasingly promoting organic farming. The objective of this activity is to produce new products from fruit waste into bioethanol and organic fertilizers that are useful for both the community and the government so that they can be used as the right solution to reduce environmental pollution and create new business opportunities. Bioethanol processing method uses Saccharomyces cerevisiae as a biocatalyst and uses an EM4 activator to produce organic fertilizers. This activity produces an output product in the form of bioethanol 46.78 % and organic fertilizer which contain 1% N.